EVALUASI KEBIJAKAN PENGELOLAAN SDM DALAM REFORMASI BIROKRASI DI BKPSDM KABUPATEN MAHAKAM ULU Oleh - Yulita Tipung; Muhammad Noor; Adam Idris; M. Aviv Adhitya Putra Pratama4 (Journal of Innovation Research and Knowledge, 2026)
Bureaucratic reform positions the management of civil servant human resources (ASN) as a strategic instrument in achieving a professional, effective, and performance-oriented bureaucracy. This study aims to evaluate policies on ASN human resource management in supporting bureaucratic reform at the Regional Personnel and Human Resources Development Agency (BKPSDM) of Mahakam Ulu Regency. The study employs a qualitative approach with a descriptive-evaluative design. Research subjects were selected purposively, including leaders and personnel involved in staffing management. Data were collected through in-depth interviews and document analysis, such as regulations, personnel documents, Employee Performance Targets (SKP), and bureaucratic reform reports. Data analysis used William N. Dunn’s policy evaluation framework, which includes effectiveness, efficiency, adequacy, equity, responsiveness, and appropriateness. The results indicate that policies have been implemented in accordance with regulations and have maintained administrative functions. However, they have not been fully effective in improving individual and organizational performance. Implementation remains procedurally oriented, while competency development has not been fully based on organizational needs. These findings highlight that policy success should be measured by its impact on performance and the achievement of bureaucratic reform goals.